A Circular Economy Use of Durian Rind Waste for Cellulose Extraction and Its Application in Polylactic Acid (PLA) Biodegradable Composites - Petchwattana, Nawadon; Cha-aim, Kamonchai; Rodphool, Khanet; Sang-on, Puttaraksa; Lapsarn, Tuangphon; Sanetuntikul, Jakkid; Sophonputtanaphoca, Supaporn (Trends in Sciences, 2025)
Durian rind is a food waste by-product left after consuming fruit flesh and can contribute to environmental pollution due to its slow decomposition and the large disposal area required because of its bulky shape. This study aims to evaluate the potential of durian rind as a cellulose source for producing biodegradable composites. Cellulose was extracted from the sample using a single-step alkali and hydrogen peroxide pretreatment under different conditions (temperature, residence time, and H2O2 concentration). The optimal condition for achieving the highest cellulose content with minimal lignin contamination was treatment with 5 % NaOH in 7.5 % H2O2 at 50 °C for 5 h. The extracted cellulose was milled and sieved to obtain 3 different particle sizes (< 250 µm (S), 250 - 425 µm (M), and > 425 µm (L)). All cellulose samples were characterized to determine their chemical and physical properties. FTIR spectra confirmed that most impurities in the raw material were removed after extraction. To evaluate the composite properties, polylactic acid (PLA)/cellulose composites with varying cellulose particle sizes and loadings were analyzed and compared to neat PLA. An increase in Young’s modulus was observed with the addition of cellulose, with the effect being more pronounced at lower cellulose loadings. Conversely, higher cellulose content negatively affected the composite properties, reducing tensile strength and elongation at break. This adverse effect was more significant with larger cellulose particles. FE-SEM analysis revealed that larger cellulose particles created larger interfacial voids, contributing to a decrease in tensile elongation at break. The incorporation of cellulose into PLA slightly elevated the glass transition temperature by approximately 1 - 2 °C. Moreover, the degree of crystallinity (Xc) significantly increased with the addition of cellulose, with smaller cellulose particles being more effective in enhancing Xc. PLA/cellulose composites may be suitable for applications as single-use plastics. HIGHLIGHTS A single-step alkali and hydrogen peroxide pretreatment under relatively mild conditions effectively extracted cellulose from durian rind. Cellulose particle size and loading content significantly influenced the mechanical and thermal properties of PLA composites. Although incorporating larger cellulose particles reduced tensile strength and elongation, PLA/cellulose composites remain suitable for single-use applications with distinct advantages. Durian rind presents strong potential as a sustainable and abundant cellulose source for bio-based material development. GRAPHICAL ABSTRACT